Analysis of heat revenues in the passenger salon of a high-speed railway car in hot conditions - Хлистун, О. Л. (Proceedings of National Aviation University (archive), 2002)
The analysis of heat input to the passenger compartment in hot conditions was carried out to determine the required cooling capacity of the air conditioning system. Considered the receipt of heat from the fresh air, through the enclosing structures, windows, from the fan, heat dissipation of people. The flow of heat through the enclosing structures is determined based on their multi-layer and the presence of an air gap. Completed for typical conditions, the calculations indicate that the contributions of the individual components of the heat input and the required capacity of the air conditioning system as a whole substantially depend on the number of passenger seats in the car.